Fluxus as Neo-Dadaism: Influences and Differences of the Fluxus and Dadaism Movements - Alireza Asyaban, Ahmad Ebrahimipour, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Fluxus was an inter-media movement established in the 1960s, which was mostly influenced by the artistic approach of the contemporary musician John Cage, featuring many of the Neo-Dadaism styles. This article, which used historical and analytical methods, aimed to revisit and analyze Neo-Dadaism tendencies in the Fluxus movement, and to distinguish it from the earlier forms of Dadaism. The most important Neo-Dadaist themes represented in the works of Fluxus artists include opposition to sensory aesthetics and the replacement of lived art, opposition to the established social values, the development of Merz’s style to open up the boundaries of artistic experience, creation of a link between art and life, bridging the gap between the artist and audience, and linking of visual arts with time and place. Dadaism and Fluxus were both affected by the aftermath of wars; however, dadaism responded by destruction to chaos, while Fluxus sought to heal the agonies and pains in many ways. Dada argued that art was not required to be beautiful and that beauty was already dead (e.g., Tzara), while Fluxus maintained that any object could be a work of art and anyone an artist (e.g., Maciunas). Dadaists often used assemblage methods, while the Fluxus artists chose the installation (arrangement) art styles. The works of the Fluxus artists only become meaningful by the time-and space-based experience of the audience, while Dadaist artists only emphasized the absurdity of their works.